Vertically Ordered Mesoporous Silica-Nanochannel Film-Equipped Three-Dimensional Macroporous Graphene as Sensitive Electrochemiluminescence Platform - Gong, Jiawei; Tang, Hongliang; Luo, Xuan; Zhou, Huaxu; Lin, Xueting; Wang, Kailong; Yan, Fei; Xi, Fengna; Liu, Jiyang (Frontiers in Chemistry, 2021)
Three-dimensional (3D) electrochemiluminescence (ECL) platform with high sensitivity and good anti-fouling is highly desirable for direct and sensitive analysis of complex samples. Herein, a novel ECL sensing platform is demonstrated based on the equipment of vertically-ordered mesoporous silica-nanochannel films (VMSF) on monolithic and macroporous 3D graphene (3DG). Through electrografting of 3-aminopropyltriethoxysilane (APTES) onto 3DG as molecular glue, VMSF grown by electrochemically assisted self-assembly (EASA) method fully covers 3DG surface and displays high stability. The developed VMSF/APTES/3DG sensor exhibits highly sensitized ECL response of tris(2,2’-bipyridyl) ruthenium (Ru(bpy)32+) taking advantages of both the high active area and conductivity of 3DG and the strong electrostatic enrichment of charged VMSF nanochannels. The VMSF/APTES/3DG sensor is applied to sensitively detect an important environmental pollutant (4-chlorophenol, with limit of detection or LOD of 30.3 nM) in term of its quenching effect (ECL signal-off mode) towards ECL of Ru(bpy)32+/tri-n-propylamine (TPrA). The VMSF/APTES/3DG sensor can also sensitively detect the most effective antihistamines chlorpheniramine (with LOD of 430 nM) using ECL signal-on mode because it acts as co-reactant to promote the ECL of Ru(bpy)32+. Combined with the excellent antifouling ability of VMSF, the sensor can also realize the analysis of actual environmental (lake water) and pharmaceutical (pharmacy tablet) samples. The proposed 3D ECL sensor may open new avenues to develop highly sensitive ECL sensing platform.